2015
DOI: 10.1177/0363546515614315
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Determinants of Return to Play After Anterior Cruciate Ligament Reconstruction in National Collegiate Athletic Association Division I Soccer Athletes

Abstract: Collegiate female soccer athletes have a high initial return-to-play rate. Undergoing ACL reconstruction earlier in the college career as well as the presence of a scholarship had a positive effect on return to play. Surgical factors including graft type, fixation method, tunnel placement technique, concomitant knee surgeries, and revision status demonstrated no significant effect on the return-to-play rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 38 publications
4
34
0
2
Order By: Relevance
“…French alpine skiers who were younger at the time of injury were more likely to improve their performance after returning to sport 36. Playing position was not a significant determinant of returning to sport in American football,33 women’s basketball32 or women’s college soccer,39 but Sikka et al 37 found that NHL defenders were more likely to return to their previous level of performance than forwards and wings.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…French alpine skiers who were younger at the time of injury were more likely to improve their performance after returning to sport 36. Playing position was not a significant determinant of returning to sport in American football,33 women’s basketball32 or women’s college soccer,39 but Sikka et al 37 found that NHL defenders were more likely to return to their previous level of performance than forwards and wings.…”
Section: Resultsmentioning
confidence: 97%
“…Concomitant injuries to menisci were associated with shorter careers among NHL players,37 but no other studies found that concomitant injuries significantly affected return to sport rates 18 21 29 39. Daruwalla et al 21 found that autografts were associated with higher rates of return to sport than allografts, but two other studies did not find any significant association between graft types and return to sport rates39 or postsurgery performance 37. Among elite baseball players, ACL reconstruction to the rear batting leg was associated with decreased batting average on return to sport 25.…”
Section: Resultsmentioning
confidence: 99%
“…de las demás investigaciones3,[13][14][15][16][17] se mantienen entre los valores de 60-80%. De aquellos participantes que no completaron el RPD, se alegaron tanto razones relacionadas con la rodilla como hinchazón, dolor14 , falta de confianza o miedo a nuevas lesiones 2 , como motivos no relacionados con el estado de la articulación como cuestiones personales16 .Otro aspecto a tener en cuenta es el nivel de profesionalización de los deportistas en el momento de la lesión y a la hora del regreso al deporte.…”
unclassified
“…A la hora del RPD tras la reconstrucción, no todos los participantes lo pueden hacer al mismo nivel previo a la lesión. En el estudio de Howard et al15 sólo el 75% vuelve a la misma categoría mientras que en otros cuatro estudios sí consiguen completar el RPD en el mismo nivel10,14,16,17 .En relación al rendimiento, sólo lo analizan tres estudios[17][18][19] . Se indica que no hay diferencias significativas entre el nivel anterior y posterior a la lesión17 , ni tampoco hubo deficiencias en la…”
unclassified
“…, soccer players returned to sports between 6 and10.2 months postoperatively;Howard et al (2016);Zaffagnini et al (2014). An analysis of Union of European Football Associations (UEFA) elite male soccer players showed a mean injury lay-off until return to unrestricted soccer practice of 202 ± 69 days for 43 European players and 203 ± 70 days for 20 Swedish players(Waldén et al, 2011) Schiffner et al (2018).…”
mentioning
confidence: 99%